Change in home bias due to ghost games in the NFL - Stephan Starke; Lars Vischer; Alexander Dilger (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2022)
We analyse changes in the National Football League (NFL) due to ghost games in 2020. The home bias disappears as expected. However, referee decisions do not seem to be relevant for this. There are also no significant results for semi-ghost games with a reduced number of spectators. – – Wir analysieren Veränderungen in der National Football League (NFL) aufgrund von Geisterspielen im Jahr 2020. Der Heimvorteil verschwindet wie erwartet. Schiedsrichterentscheidungen scheinen dafür aber nicht relevant zu sein. Auch für partielle Geisterspiele mit reduzierter Zuschauerzahl gibt es keine signifikanten Ergebnisse.
Keywords: Z20; 650